The structural properties of a ZnCl2–ethylene glycol binary system and the peculiarities at the eutectic composition. Issue 23 (2nd June 2021) - Kalhor, Payam; Ghandi, Khashayar; Ashraf, Hamad; Yu, Zhiwu
Abstract : FTIR spectroscopy and quantum chemical calculation were used to investigate a series of ZnCl2 –ethylene glycol (EG) mixtures, including the stable ZnCl2 –4EG deep-eutectic solvent, to explore the structural heterogeneity and hydrogen bonding properties. Abstract : ATR-FTIR spectroscopy was performed on a series of ZnCl2 –ethylene glycol (EG) mixtures with a wide-range of compositions (1 : 1.5–1 : 14 in molar ratios), involving the stable ZnCl2 –4EG deep-eutectic solvent (DES) composition, to explore the spectral variations, structural heterogeneity, and hydrogen bonding (H-bonding) properties. To enhance the resolution of the spectra, excess absorption and two-dimensional correlation spectroscopies were employed. In the initial IR spectra, a quasi-isosbestic point was identified, signaling that the major disturbance on EG microstructures by adding ZnCl2 is to form a distinct complex. Further analysis uncovered the main transformation process to be from the EG tetramer to the ZnCl2 –4EG complex. It was also found that as the EG content increases, negative charge increasingly transfers to ZnCl2, resulting in the strengthening of the Zn ← O coordination bonds and the weakening and finally dissociation of Zn–Cl bonds. Regarding the ZnCl2 –4EG DES, several incomparable specificities were observed. It was found that ZnCl2 destructed the H-bonding network of pure EG to the largest extent, resulting in the highest production of the dimer and trimer of EG. Moreover, in comparison with other compositions, the ZnCl2 –4EG DES showed abrupt increases in the negative charge of the salt, the length of the Zn–Cl bond, and the strength of the Zn ← O coordination bond. All these imply the strongest intermolecular interactions and the highest solvation of ZnCl2 in EG at the eutectic composition compared to those of other mixtures, resulting in a super-stable liquid mixture. The work provides physical insights into the structural and interactive properties of deep-eutectic solvents.